Erosive Pustular Dermatosis of the Scalp After Excision and Skin Grafting of Scalp Squamous Cell Carcinoma - Xun He; Chao-Qun Wang; Wei Lu; Yu-Gang Gong; Xiao-Wei Sha; Zhu Shen (Wolters Kluwer Health, 2021)
Abstract. Introduction:. Erosive pustular dermatosis of the scalp (EPDS) is an uncommon condition with unknown etiology. The clinical exclusive diagnosis needs to be differentiated from similar diseases. Here, we present a case of EPDS after surgical treatment of scalp squamous cell carcinoma. Case presentation:. A 68-year-old woman presented with an eight-month history of a chronic scalp eruption. She had been diagnosed as squamous cell carcinoma by biopsy nine months ago, and had been treated by surgical excision and skin grafting. One month later, she was referred for evaluation of the newly enlarged lesion which was observed at the skin grafting site. She was diagnosed of EPDS based on characteristics of lesions, clinicopathological findings and laboratory data. The condition had clinically improved with systemic steroid therapy and topical tacrolimus for two weeks. Relapses occurred after complete withdrawal of both treatments. After repeating the above therapy and applying topical tacrolimus as maintenance therapy, the condition was well controlled at the one-year follow-up. Discussion:. EPDS is an uncommon inflammatory dermatosis with main incidence rate of elderly patients and female predominance. The diagnosis of EPDS cant be made only by histopathological examination, which is helpful for differential diagnosis. Microbiological investigations commonly remain negative. For the high risk of relapse, it is important for clinicians to be aware of maintenance treatment and a long- term management. Conclusion:. It should be recognized by clinicians that EPDS is an uncommon and relapse disease, leading to serious cosmetic problems. The treatment lacks evidence-based medicine data, clinician should choose the appropriate therapy according to the condition of patients.